Dessecação em pré-colheita com glifosato e qualidade de sementes armazenadas de soja - Toledo, Mariana Zampar; Ishizuka, Mariane Sayuri [UNESP]; Cavariani, Cláudio [UNESP]; Franca-Neto, Jose de Barros; Picoli, Lais Bilia [UNESP] (Univ Estadual Londrina, 2014)
Seeds from non-genetically modified soybean cultivars harvested after chemical desiccation of plants with glyphosate may produce abnormal seedlings; these may show phytotoxicity symptoms that could persist even after some time of storage due to accumulation of toxic residues. This study aimed to evaluate the quality of stored soybean seeds harvested after chemical desiccation of plants with glyphosate at R7 stage. Seeds from soybean cultivar 'Conquista' were produced with and without desiccation with glyphosate, at the dose 2.0 L ha(-1), applied at physiological maturity stage. Seed quality was evaluated right after harvest and after eight months of storage by tests of moisture content, mass, germination and vigor. The experimental design was the completely randomized block with four replications. Data was submitted to variance analysis and means were compared by the Tukey test (p <= 0.05) as a 2 x 2 factorial. The results show deleterious effects of glyphosate used as desiccant for early harvest of soybean seeds from conventional cultivars. Accelerating plant senescence leads to production of seeds with lower germination and decreased seedling development, although the percentage of abnormal seedlings is reduced after 8 months of storage possibly due to degradation of toxic residues of glyphosate and/or derivates.
Pre-harvest desiccation with glyphosate and quality of stored soybean seeds
Keywords: Glycine max; phytotoxicity; physiological maturity; germination; seedling development